(3bUI Led GdCYQGHj GdcGaQCHj eSYhO GdKbajs - (3GdHcQj, eMeO Hf eMeO Hf YHO GdQMef, J(B952(3g`s ((3eMeO GdegOGhjs)
(3ChdgG (B:s
(3bGd CHh GdMSf GdHcQj QGhj SjQI QShd Gddg Udi Gddg Ydjg hSde HjfeG QShd Gddg Udi Gddg Ydjg hSde LGdS PGJ jhe aj MLQJg hcGf YfOg GdEeGe Ydj Hf CHj WGdHs
(3BNQgG (B:s
(3bGd GdQGhj hdbO hQO Yf gPG GdLed Efg SGQM aj LHd GdeOjfI jQYi hjONd aj GdeOjfI dG CMO jJYQV Edjg MJi Jhaj QShd Gddg Udi Gddg Ydjg hSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 57s
(3eYLe GdeDdajf(B: 3 / 650s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs